Improving Students’ Writing Skill in Teaching Narrative Text by Using Indonesian Folktales - Darmayanti, Darmayanti; Hartati, Hartati; Muslimin, Fawal Fatwa; Khatimah, Nurul (Universitas Pahlawan Tuanku Tambusai, 2024)
The use of interesting teaching media aims to create enjoyable learning for students by choosing teaching materials that attract students’ interest and create interactive learning. The use of Indonesian folktales is one of the media that can be used by teachers in teaching English, especially narrative texts. The purpose of this research is to teach students writing in narrative texts through the use of Indonesian folktales to improve their’ writing skills. This research used an experimental method. There are three steps in carrying out this experimental research to obtain data: the pretest, the treatment, and the posttest. The results of this research show that the students’ ability to write narrative texts is statistically significant. There was an increase in the average score of the experimental class by 51.19 on the pretest and 80.42 on the posttest. Meanwhile, in the control class, the pretest result was 56.67 and the posttest result was 64.89 for writing narrative texts using Indonesian folktales. It can be concluded that by using Indonesian folktales, teachers can direct their students to practice a lot and increase their practice without ignoring other material, with the aim of creating effective and enjoyable learning